Prediction and Modelling of Snow Accumulation on Commercial Vehicles using CFD Simulations and Experimental Methods - Koutsimanis, Dimitrios; Sobieraj, Lukasz (My University, 2021)
Snow contamination poses great challenges for the uninterrupted operation of commercial vehicles. The purpose of this project has been to contribute towards a better understanding of the properties and mechanisms that drive snow accumulation on commercial vehicles. Computational Fluid Dynamics (CFD) tools and simple experimental methods were utilized. Initially, the idea of using only aerodynamic properties to predict snow accumulation was explored. The flow velocity was used to approximate the snow particle impact velocity and wall shear stress was used as the snow removing force. However, utilizing flow velocity proved to be challenging given the available tools and using only wall shear stress did not give accurate predictions. Therefore, a passive scalar was used to approximate snow. A method combining the passive scalar with wall shear stress was created. The performance of the method was enhanced by incorporating surface temperature data from field tests. Additionally, snow accumulation was influenced by surface orientation, i.e. the direction and inclination of the vehicle’s surfaces could either help or hinder snow packing. The method was validated against infield test data, achieving satisfactory agreement in most sections of the vehicle. Studying snow-surface interaction was deemed too complicated and therefore it was decided to substitute snow with ice cubes. Simple experiments were performed to investigate the effects of temperature and surface material, as well as the influence of adhesion on ice-surface friction. The behaviour of ice varied significantly depending on temperature and material. The effect of adhesion varied between materials, contributing to higher values of static friction coefficient around the melting point of ice. At lower temperatures the effect of adhesion was less significant. Angle of repose experiments were performed using artificially created snow. The effects of ambient tem perature, surface material and snow fall height were investigated. It was observed that as temperature increased, larger angle of repose was obtained. Additionally, an increase in fall height resulted in smaller angle of repose. Differences in the angle of repose were observed also for the different surface materials that were tested. The possibility of replicating snow with substitute materials was also assessed. It was found that the behaviour of the tested substitute materials was influenced mainly by the shape and size of their grains. A multiphase model was developed to study the physics of adhesive ice particles in detail. Discrete Ele ment Method was chosen as the most suitable framework. Data obtained from the experiments were utilized to allow for a direct comparison between the CFD and test results. Sensitivity analysis was performed for inter-particle static friction coefficient, tangential restitution and rolling resistance model. It was found that an increase in inter-particle static friction coefficient resulted in a linear increase of the angle of repose. It was observed that as the tangential restitution coefficient increased, more time was needed to obtain the final angle of repose. Because all simulations had the same time limit, the angles of repose obtained in some cases were not stabilized and prevented the establishment of a trend. In the case of the rolling resistance model, it was found that the constant torque model resulted in smaller angle of repose compared to the force proportional model.
Keywords: Computational Fluid Dynamics, Discrete Element Method, Commercial Vehicles, Snow Contamination, Angle of Repose, Adhesion, Multiphase Flow